Current Status of Sexing Bovine Spermatozoa In Indonesia - Tappa, Baharuddin (Annales Bogorienses, 2011)
The government of Indonesia has launched a Program Self-Sufficiency for Beef and Buffalo in Year 2014 (PSDS/K-2014). The objectives of this program include increasing population, improving productivity and increasing beef production, and increasing farmer income and welfare. To achieve the increasing population, the availability of elite cows is required. Currently, the main problem of development cattle in Indonesia is limited number of elite cows in terms of both quantitative and qualitative. One thing that needs to be done to achieve the program is an increase in the genetic quality and capacity through improved livestock production and productivity of livestock including use sexing sperm for artificial insemination (AI). The main application of sexed sperm to date has been to breed dairy heifers to produce female calves. To have calves with the sex according to the expectation, for example, female calve, we can perform the separation of sperm carrying the X chromosome so that the fertilized egg finally will become a female calve. Several methods have been performed to obtain optimal results and decent AI. Research Center for Biotechnology LIPI since 1999 until now, generate 70-90% of sperm Y. The results obtained by concentration of 5% and 10% is the ratio of the concentration of sperm that optimum separation column can be separated by 70-88% X sperm and Y sperm by 70-90%. Sperm motility before and after separation (sexing) is not too early for motility decreased from 76-80% to 67-80%. Difference increasing concentrations of BSA is expected to separate the spermatozoa that have a high motility (spermatozoa Y) will be able to penetrate the concentration of the more dense medium separation, whereas the X sperm will remain in the media that has a lower concentration. Generally indicates that, the separation of sperm quality after freezing is still fit for use for AI is characterized by sperm motility is still around 40-50%. After calves birth, offspring from sexed spermatozoa appear to have no more abnormalities than control spermatozoa. No significant effect on male calf and female calf at birth and weaning. Therefore, there appear to be no detrimental effect of sorting spermatozoa on resulting spermatozoa. Successful use of sexed sperm requires excellent management of cattle, careful handling of sperm and use of skilled inseminators.